Flerspråkiga fackordböcker inom juridik och ekonomi – till skada eller till nytta? - Rossenbeck, Klaus (Nordiske Studier i Leksikografi, 2003)
This article deals with problems of multilingual LSP lexicography in the fields of law and economics/business administration. After a short overview of models multilingual dictionaries might be based on (they can be intended to function as monodirectional, bidirectional or multidirectional dictionaries) we discuss problems of equivalence, especially in bidirectional and multidirectional dictionaries in culture-bound fields like law and economics/business administration. The demands multilingual LSP dictionaries should meet are here related to those on bilingual (monodirectional) dictionaries. Combining theoretical reflections with the analysis of how existing multilingual dictionaries proceed, the conclusion is drawn that little can be gained from preparing multilingual dictionaries of law and economics/business administration; rather one should concentrate on more useful monodirectional bilingual dictionaries instead.